Literature Review of Research on Influential Factors on Community Music Participation of Elderly Groups in Chengdu City - Wang, Funan; Khatibi, Abdol Ali; Tham, Jacquline (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
As aging increases in Chengdu, community music, as an important vehicle for promoting mental health and alleviating social isolation among the elderly, has become a key issue in the construction of an “all-age-friendly” city. In this paper, we review the literature on community music participation in Chengdu and explore the implications of the factors affecting community music participation among older adults, categorized by community development and function, problems and suggestions, and factors affecting community music participation.